Treatment seeking behavior among post-menopausal females attending out-patient clinic of Obstetrics and Gynecology at a tertiary care centre, Bhopal, Madhya Pradesh - Singh, Nisha; Chouhan, Yogendra; Patel, Seema (International Journal Of Community Medicine And Public Health, 2018)
Background: Onset of menopause causes a variety of somatic, sexual, vasomotor and psychological manifestations which can deteriorate the quality of life of women. According to sample registration system (SRS) 2014, the proportion of women aged 45-59 years is 15.3% and thus it is imperative for healthcare providers to focus more attention on the health of postmenopausal women. In India, however this phase of life is generally ignored. The objectives of the study were to determine the health seeking behavior of postmenopausal women with respect to the problems faced during menopause and to determine the utilization pattern and barriers to utilization of health care services. Methods: Prospective cross-sectional study for one year period starting from 1 July 2015 to 30 June 2016. Data collected using Systematic Random Sampling from 255 postmenopausal women and entered into MS excel 2007. Analysis done with Epi-Info 7.2. Chi- square applied as statistical test of significance and p<0.05 considered to be statistically significant. Results: In present study, majority (73.33%) participants did not take any treatment. 10.98% and 6.67% gave history of self medication and use of home remedies, respectively. Statistically significant correlation was found between treatment taken and factors like residing locality, education and socio-economic class. The most common reason for delayed or no treatment seeking was unawareness, followed by financial issues. Conclusions: Majority postmenopausal women faced one or more problems associated with menopause but very few sought treatment. Lack of knowledge and financial constraints were found to be major barriers to utilization of health services.